Two cases of complicated jejunal diverticulosis in a low-resource peripheral teaching hospital - Dar, Salman Farooq; Maria Mehmood; Adnan Zafar; Shah, Saleem Raza; Muhammad Ateeq (Journal of the Pakistan Medical Association, 2022)
Jejunal diverticula, like other intestinal diverticula, can become complicated and present as acute abdomen. Diagnosis is difficult and management in complicated cases can be surgical as well as conservative. We present two cases of complicated jejunal diverticulosis that presented with acute abdomen and were managed surgically. Post-operative recovery was satisfactory. Jejunal diverticula is a diagnostic challenge in a low-resource peripheral hospital. Keywords: Jejunal diverticula, Perforation, Low-resource hospital, Diverticulitis.